Pengaruh Disiplin Kerja, Lingkungan Kerja, dan Semangat Kerja terhadap Prestasi Kerja Warga SMP Perintis, Kecamatan Pancoran Mas Kota Depok - Soelehan, Aan; Sukartaatmadja, Iswandi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
Work discipline, work environment, and work spirit variables have significant influence towards teachers and employeesâ performance at SMP Perintis, Pancoranmas Subdistrict, Depok municipality. F-count is higher than F-table (5,118 > 3,13). Work spirit has dominant influence towards teachers and employeesâ performance (t-count > t-table). Work discipline has significant influence towards performance (t-count 2,295 > t-table 1,729 by means of test point Î± = 5%). It means that significant influence abides. By reliability as high as 1,729, performance can be increased as high as 0,4032.Work environment variable has just low influence towards performance (t-count 0,433 < t-table 1,729 by means of test point Î± = 5 %). Job satisfaction variable has significant influence towards performance (t-count 2,759 < t-table 1,729 by means of test point Î± = 5%). Key Words : Work discipline, work environment, and work spirit;